Correlation of Alberta Stroke Program Early Computed Tomography Score With Computed Tomography Perfusion Core in Large Vessel Occlusion in Delayed Time Windows. Issue 2 (February 2021) - Voleti, Sriharsha; Vidovich, Johnathan; Corcoran, Brendan; Zhang, Bin; Khandwala, Vivek; Mistry, Eva A.; Khatri, Pooja; Tomsick, Thomas; Vagal, Achala
Abstract : Background and Purpose: The Alberta Stroke Program Early Computed Tomography (CT) Score (ASPECTS) and CT perfusion (CTP) are commonly used to predict the ischemic core in acute ischemic strokes. CT angiography source images (CTA-SI) can also provide additional information to identify the extent of ischemia. Our objective was to investigate the correlation of noncontrast CT (NCCT) ASPECTS and CTA-SI ASPECTS with CTP core volumes. Methods: We utilized a single institutional, retrospective registry of consecutive patients with acute ischemic stroke with large vessel occlusion between May 2016 and May 2018. We graded ASPECTS both on baseline NCCT and CTA-SI and measured CTP core using automated RAPID software (cerebral blood flow <30%). We used Spearman's correlation coefficients to evaluate the correlation between continuous variables. Results: A total of 52 patients fit the inclusion criteria of large vessel occlusion in 6 to 24 hours and baseline imaging work up of NCCT, CTA, and CTP. The median age was 63 (interquartile range=53.5–75) and 38.46% were female. The median NCCT ASPECTS was 7 (interquartile range=6–9), CTA-SI ASPECTS was 5 (interquartile range=4–7), and CTP core was 14.5 mL (interquartile range=0–46 mL). There was a moderate correlation between NCCT ASPECTS and CTP core (rs =−0.55, P <0.0001) and between CTA-SI ASPECTS and CTP core (rs =−0.50, P =0.0002). The optimal NCCT ASPECTS cutoff score to detect CTP core ⩽70 mL was ≥6 (sensitivity, 0.84; specificity, 0.57; positive predictive value, 0.93; negative predictive value, 0.36) and the optimal CTA-SI ASPECTS was ≥5 (sensitivity, 0.76; specificity, 0.71; positive predictive value, 0.94; negative predictive value, 0.31). Conclusions: There was a moderate correlation between NCCT and CTA-SI ASPECTS in predicting CTP defined ischemic core in delayed time windows. Further studies are needed to determine if NCCT and CTA imaging could be used for image-based patient selection when CTP imaging is not available. Abstract : Supplemental Digital Content is available in the text.